Schauder bases in an abstract setting (2002)
By using some generalized Riemann integrals instead of ordinary sums and multiplication systems of Banach spaces instead of Banach spaces, we establish some natural generalizations of the most basic facts on Schauder bases so that Hamel bases, and some other important unconditional bases, could also be included.